INFLUENCIA DE LA CONGRUENCIA, CONFIANZA Y COMPROMISO EN LA RECOMENDACIÓN DE MARCA DE UNA MARATÓN - Alguacil Jiménez, Mario; Martínez Cevallos, Daniel Alejandro; Calabuig Moreno, Ferran (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
This research sought to verify through a proposal of a predictive model, if the variables of congruence, confidence and commitment can be considered significant predictors of the recommendation or WOM and, if so, to what extent they do so. To obtain the information, a validated measuring instrument was used, made up of scales that were adapted from previous studies. For the analysis of the results, the statistical program SPSS was used, in its version 25. First, a descriptive analysis of the results was carried out, and then a correlation analysis of Pearson was carried out to check the independence of the predictor variables. Finally, a linear regression model was created, with the intention of testing whether the variables presented predicted in a significant way the recommendation of the participants of the event and, if so, what influence each one has. The results indicate that all variables significantly predict the recommendation, with compromise being the most important element (β=.30; p<.01), followed by congruence (β=.28; p<.01) and confidence (β=.20; p<.05), where the proposed model as a whole is capable of explaining 48% of the variance of the recommendation.